2019
DOI: 10.18027/2224-5057-2018-8-4-45-49
|View full text |Cite
|
Sign up to set email alerts
|

Association of XRCC1, HMMR genes with breast cancer in the Kyrgyz ethnic group

Abstract: An association of genes XRCC1 and HMMR with breast cancer (BC) has never been tested in the Kyrgyz ethnic group. This was a case-control study of 201 women of the Kyrgyz ethnic group with a morphologically verified breast cancer (N=99) and 102 controls age-matched with BC cases. The mean age of the patients was 53 years (24–74, SE mean = 0.967, STD=9.81). The extraction of DNA was carried out from venous blood. The genotyping was conducted by using the method of polymerase chain reaction and restriction fragme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The efficiency of DNA repair in cells is one of the determining factors in preventing the development of cancer [15]. It has been suggested that functional disruptions in highly conserved DNA repair processes resulting from polymorphic variations may increase genetic susceptibility to breast cancer (BC) [10,16,17].…”
Section: Resultsmentioning
confidence: 99%
“…The efficiency of DNA repair in cells is one of the determining factors in preventing the development of cancer [15]. It has been suggested that functional disruptions in highly conserved DNA repair processes resulting from polymorphic variations may increase genetic susceptibility to breast cancer (BC) [10,16,17].…”
Section: Resultsmentioning
confidence: 99%